Satire and Social Criticism in Jane Austen's Pride and Prejudice - Ahmed Saeed Ahmed Mocbil (مجلة الدراسات الاجتماعية)
This study investigates the role of satire and social criticism in Jane Austen's Pride and Prejudice, focusing on how Austen's narrative techniques illuminate the absurdities and constraints of early 19th-century English society. Through a qualitative analysis, this research explores key themes of class structure, gender roles, and marriage conventions, demonstrating how Austen's characters and dialogues both entertain and provoke critical reflection. By examining specific instances of satire, this paper aims to deepen the understanding of how Austen's work serves as a significant commentary on social issues of her time, enhancing the enduring relevance of Pride and Prejudice in contemporary literary discourse.